Technical Variables Affecting to the Production of Dried Herb Tea from Callisia Fragrans - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2019)
C. fragrans is a herbaceous plant with small white fragrant flowers and waxy leaves. C. fragrans leaves contain biologically active components such as flavonoids, neutral glycol-and phospholipids and fatty-acids.The aim of this work was to evaluate the effect of blanching, drying and preservation on the free radical scavenging activity and total phenolic content of dried Callisia fragrans. By examining on different variables of the blanching, drying; the highest phenolic and antioxidant activity inside the dried Callisia fragrans could be achieved by blanching within 10 seconds, at 95oC in the presence of citric acid 4%; size of Callisia fragrans 2.0 cm; drying at 50oC by heat pump dryer until the final moisture content 6.5%. The dried Callisia fragrans may be stable for 12 months in PET/AL/PE bag at 25oC without any deterioration. The study was of great importance to generate information about the blanching and drying process in preserving herb quality and bioactivity by avoiding the degradation of metabolites.Keywords: Callisia Fragrans, Blanching, Citric acid, Drying, Phenolic, antioxidant.